Delineation of groundwater aquifer and salt front in coastal areas (case study Delta Wadi El-Arish, Sinai, Egypt) - MEKHEMER, Hatem M.; ABD ALLA, Mohamed A. (Contributions to Geophysics and Geodesy, 2021)
The Sinai area attracted the government to set a national plan for its sustainable development. Since the major problem facing the construction of new communities in Sinai generally, and in El Arish, is the source of water. This work represents a part of extensive field program for groundwater evaluation that was planned and executed by WRRI since 1982. The objective of this work is to develop the area to become attractive for population and reclamation. This study includes geological and hydrogeological studies besides forty eight vertical electrical sounding (using the Schlumberger arrangement) that were measured in the north part of El Arish, in order to investigate the Quaternary groundwater aquifer systems. A special care was directed towards groundwater investigations, to be used later for domestic and irrigation purposes. The present work is selected to show the drawbacks of the effect of saltwater intrusion on the groundwater potentiality. These VESes have been interpreted both qualitatively and quantitatively using geoelectrical cross-sections. Correlation of the deduced geoelectric and hydrogeological parameters with the available geological information helped in establishing the specific resistivities of the formations. The results revealed that there are three main geoelectrical units. The second and third geoelectric layers represent is water bearing formations, but they are not connected under all VES. The third geoelectrical unit is affected by salt-water intrusion.